Acoustic Study of REpower MM92 Wind Turbines During Exploitation - KŁACZYŃSKI, Maciej; WSZOŁEK, Tadeusz (Archives of Acoustics, 2014)
The paper presents the current state of knowledge concerning the sources of noise generated by wind turbines, force measurement methodology, and assessment of noise onerousness in this type of installation, on the basis of a study concerning a wind farm with five REpower MM92 wind turbines and the electric power of 2 MW and the sound power level of 104.2 dB(A) each. Particular attention was focused on the often discussed problem of presence of infrasound generated by turbines and on the requirements of the applicable reference methodologies for the measurement of wind speed to 5 m/s, while the turbine reaches its full power at speeds above 10 m/s.